«Ulisse coperto di sale». Roversi e Dalla - Marchionne, Mario (L’ospite ingrato, 2024)
The article tries to take stock of a little-studied aspect of Roberto Roversi’s activity, namely the partnership with Lucio Dalla. Between 1973 and 1976 the two artists created three important albums in the field of Italian song. The contribution highlights the most significant moments, both from the point of view of the construction of the songs and the content choices. Central is the attention relating to the problem of communication, of the public, of the final meaning of this “daring” operation, that is, writing songs in which music and text are combined equally: neither the music nor the text act as accompaniment. In the three albums different realities emerge aimed at drawing some moments of our history and everyday life, with an almost anthropological attention, capable of digging deep, enhancing the singing and musical skills of Lucio Dalla.